Modern Weapons and Military Equipment for Issue 1/2014 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Czech Aero star development of L-169 trainer; Scorpion light attack jet performs maiden flight; New M-345 HET trainer revealed; Turkish attack helicopter again in delay; India’s LCA Tejas reaches IOC; Iran reveals UCAV Fotros; Integration of Meteor missile onto Gripen E agreed; French MoD and MBDA signed development and production contract for antitank system Moyenne Portee; UK invests 79 million Pounds into development of new generation submarines; German Iris-T SL surface-to-air missile successful trails; Alexander Nevsky submarine enters into operation with the Russian Navy; Maiden flight of Chinese Z-20 helicopter; F-35’s first live AMRAAM firing; KAI reveals model of the new version of its KFX fighter; Lockheed’s Skunk Works reveals SR-72; India’s DRDO presents tactical ballistic missile Pragati; Sikorsky Innovations wins contract for VTOL experimental aircraft; Jordanian gunship CN235 performs maiden flight; General Atomics shows its EMRG railgun; Aurora too wins contract for Phase I of VTOL X-Plane program; Airbus Military reveals more details on new Fire-fighter; US proposal of weapons and equipment for Romanian F-16A/B; Russia to develop light-weight front-line fighter; Start of Eurofighter cruise missile integration trails.